2017
DOI: 10.1002/pen.24571
|View full text |Cite
|
Sign up to set email alerts
|

Infrared thermography to locate impact damage in thin and thicker carbon/epoxy panels

Abstract: This work is concerned with the use of infrared thermography (IRT) to investigate impact damaging of carbon/epoxy materials. IRT has already proved suitability to visualize thermal effects induced by impact tests, but till now it has been mainly used with thin laminates with little attention toward the thicker ones. The aim of this work is to compare thermal effects evolving on both thin and relatively thick laminates to better validate the use of IRT and to get information useful for the comprehension of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…There is ongoing research on other non-destructive testing (NDT) techniques for more accurate evaluation and convenient implementation, such as acoustic emission (2)(3)(4)(5)(6)(7)(8) , guided waves (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) (e.g. piezoelectric transducer-based (19,20) and angle beam transducer-based (21,22) ), air-coupled ultrasonics (23)(24)(25)(26)(27)(28)(29)(30) , thermography (31)(32)(33)(34)(35)(36) , optical fibre sensing (37)(38)(39)(40)(41)(42) , digital image correlation (DIC) (43)(44)(45)(46)(47)(48) , electromagnetic testing (49)(50)…”
Section: Introductionmentioning
confidence: 99%
“…There is ongoing research on other non-destructive testing (NDT) techniques for more accurate evaluation and convenient implementation, such as acoustic emission (2)(3)(4)(5)(6)(7)(8) , guided waves (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) (e.g. piezoelectric transducer-based (19,20) and angle beam transducer-based (21,22) ), air-coupled ultrasonics (23)(24)(25)(26)(27)(28)(29)(30) , thermography (31)(32)(33)(34)(35)(36) , optical fibre sensing (37)(38)(39)(40)(41)(42) , digital image correlation (DIC) (43)(44)(45)(46)(47)(48) , electromagnetic testing (49)(50)…”
Section: Introductionmentioning
confidence: 99%
“…Boccardi et al. 7 utilized infrared thermography to research the impact damage behaviors of laminates and found that in thinner laminates occurred permanent damage at low impact energy. Curtis et al.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, extensive studies have been carried out to investigate the damage initiation and propagation of composites under out-of-plane impact. Boccardi et al 7 utilized infrared thermography to research the impact damage behaviors of laminates and found that in thinner laminates occurred permanent damage at low impact energy. Curtis et al 8 studied the damage, deformation and residual burst strength of composite tubes subjected to impact and quasi-static indentation, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have investigated the impact damage and response of CFRP laminate. He et al [18][19][20], Petronyuk et al [21] and Boccardi et al [22] have done considerable research on the nondestructive testing methods of composite laminate subjected to impact loads through the techniques of pulsed eddy current (PEC), impulse acoustic microscopy and infrared thermography. Jang et al [23][24][25][26] has investigated the impact signals obtained from the high-speed fiber Bragg grating (FBG) sensor system on CFRP laminates.…”
Section: Introductionmentioning
confidence: 99%